Modified ABCDEF-Bundles for Critically Ill Pediatric Patients - What Could They Look Like? - Engel, Juliane; von Borell, Florian; Baumgartner, Isabella; Kumpf, Matthias; Hofbeck, Michael; Michel, Jörg; Neunhoeffer, Felix (Frontiers in Pediatrics, 2022)
Background and significance Advances in pediatric intensive care have led to markedly improved survival rates in critically ill children. Approximately 70% of those children survive with varying forms of complex chronic diseases or impairment/disabilities. Length of stay, length of mechanical ventilation and number of interventions per patient are increasing with rising complexity of underlying diseases, leading to increasing pain, agitation, withdrawal symptoms, delirium, immobility, and sleep disruption. The ICU-Liberation Collaborative of the Society of Critical Care Medicine has developed a number of preventative measures for prevention, early detection or treatment of physical and psychiatric/psychological sequelae of oftentimes traumatic intensive care medicine. These so called ABCDEF-Bundles consist of elements for (A) assessment, prevention and management of pain, (B) spontaneous awakening and breathing trials (SAT/SBT), (C) choice of analgesia and sedation, (D) assessment, prevention and management of delirium, (E) early mobility and exercise and (F) family engagement and empowerment. For adult patients in critical care medicine, research shows significant effects of bundle-implementation on survival, mechanical ventilation, coma, delirium and post-ICU discharge disposition. Research regarding PICS in children and possible preventative or therapeutic intervention is insufficient as yet. This narrative review provides available information for modification and further research on the ABCDEF-Bundles for use in critically ill children. Material and methods A narrative review of existing literature was used. Results One obvious distinction to adult patients is the wide range of different developmental stages of children and the even closer relationship between patient and family. Evidence for pediatric ABCDEF-Bundles is insufficient and input can only be collected from literature regarding different subsections and topics. Conclusion In addition to efforts to improve analgesia, sedation and weaning protocols with the aim of prevention, early detection and effective treatment of withdrawal symptoms or delirium, efforts are focused on adjusting ABCDEF bundle for the entire pediatric age group and on strengthening families' decision-making power, understanding parents as a resource for their child and involving them early in the care of their children.